Evidence for Superhydrous Primitive Arc Magmas from Mafic Enclaves at Shiveluch Volcano, Kamchatka - Goltz A.E.; Krawczynsky M.J.; Gavrilenko M.G; Gorbach N.V.; Ruprecht Ph. (My University, 2020)
Mafic enclaves preserve a record of deep differentiation of primitive magmas in arc settings. We analyze the petrology and geochemistry of mafic enclaves from Shiveluch volcano in the Kamchatka peninsula to determine the differentiation histories of primitive magmas and to estimate their pressures, temperatures, and water contents. Amphibole inclusions in high forsterite olivine suggest that the primitive melt was superhydrous (i.e. >8 wt% H2O) and was fractionating amphibole and olivine early on its liquid line of descent. We find that the hydrous primitive melt had liquidus temperatures of 1062±48°C and crystallized high Mg# amphibole at depths of 23.6-28.8 km and water contents of 10-14 wt% H2O. The major and trace element whole rock chemistry of enclaves and of published analyses of andesites suggest that they are related through fractionation of amphibole-bearing assemblages. Quantitative models fractionating olivine, clinopyroxene, and amphibole reproduce geochemical trends defined by enclaves and andesites in variation diagrams. These models estimate 0.2%-12.2% amphibole fractionated from the melt to reproduce the full range of enclave compositions, which overlaps with estimates of the amount of amphibole fractionated from parental melts based on whole rock dysprosium contents. This contribution extends the published model of shallow processes at Shiveluch to greater depths. It provides evidence that primitive magmas feeding arc volcanoes may be more hydrous than estimated from other methods, and that amphibole is an important early fractionating phase on the liquid line of descent of superhydrous, primitive mantle-derived melts.
Keywords: 38.37.25 Вулканология; Шивелуч